Interpretasi Kontekstual Ayat Hutang (Dain) dan Relevansinya terhadap sistem transaksi keuangan modern masa kini: Kajian Hermeneutika Double Movement Fazlur Rahman - Masodi Masodi (International Conference on Islamic Economic (ICIE), 2025)
Fazlur Rahman, a modern Islamic thinker, offers the Double Movement hermeneutic method as an approach to understanding the texts of the Qur'an. This method emerged as Rahman's critique of the classical interpretation method which is considered partial and atomistic in interpreting the Qur'an. This study will focus on two research questions, namely How is the Meaning of "Dain" in QS. Al-Baqarah: 282 from Fazlur Rahman's Double Movement hermeneutic perspective and How is the relevance of the verse "Dain" in QS. Al-Baqarah: 282 to today's modern financial transaction system. This study uses a qualitative research type with a library research approach, one of the approaches used to explore information and understand certain phenomena based on existing written sources, such as books, journals, articles, research reports, and other documents. In Fazlur Rahman's Double Movement hermeneutics, "dain" is not only seen as debt in the literal sense during the time of the Prophet, but also as a moral and ethical principle that regulates clarity in financial transactions, which can be applied in the context of modern economics.